EZH2-activating mutation: no reliable indicator for efficacy of methyltransferase inhibitors. Issue 12 (14th October 2020) - Quentmeier, Hilmar; Pommerenke, Claudia; Hauer, Vivien; Uphoff, Cord C.; Zaborski, Margarete; Drexler, Hans G.
Abstract: EZH2 gain of function mutations (EZH2 GOFmu ) has been implicated in the pathogenesis of B-non-Hodgkin lymphoma. The EZH2-specific inhibitor GSK126 inhibits trimethylation of histone H3K27 and induces target gene expression. However, in 3/4 EZH2 GOFmu B-NHL lymphoma cell lines, GSK126 (400 nM) did not induce growth arrest. Only at high doses (10 µM), the inhibitor was effective as antiproliferative agent, comparably in EZH2 GOFmu, wild-type, and EZH2 -negative cell lines, suggesting that at high concentrations, the antiproliferative effects of GSK126 are off-target effects. In sum, we could not confirm that B-NHL cell lines with EZH2 GOFmu show a higher sensitivity to GSK126 than EZH2 wild-type cell lines do. Only 1/4 EZH2 GOFmu B-NHL cell lines tested (PFEIFFER) were sensitive to GSK126 (400 nM) inducing growth arrest. If these results can be translated to patients, they raise the question of whether the presence of EZH2 activating mutations alone allows selection for targeted therapy with EZH2 inhibitors.